MACHINES FOR PRIMARY LOG CUTTING: PART I – A STUDY ON SOME OPERATIONAL INDICATORS - Atanasov, Valentin (Innovation in Woodworking Industry and Engineering design, 2024)
The paper presents experimental results obtained during the processing of logs with different machines for primary cutting of logs – a vertical band saw machine with a carriage feed mechanism (Üstünkarli – Turkey), a circular saw machine for logs (Kallion Konepaja Oy – Finland) and a mobile horizontal band saw machine (Arsov 90 Ltd. – Bulgaria). The places for conducting the research are the manufacturing conditions of Training and Experimental Forest Range "G. Avramov" – the village of Yundola, Training and Experimental Forest Range "Petrohan" – the village of Burzia and "Petnop" Ltd. – the town of Varshets. The influence of basic parameters related to processing with these machines – feed speed and cutting amount, on the quality of the obtained wood materials was determined. The evaluation metrics measured are dimensional accuracy and surface roughness. The productivity of the machines was also determined. The studied wood species was Scots pine (Pinus sylvestris L.). The obtained results were analyzed and practical recommendations were proposed.